2020
DOI: 10.7717/peerj.10052
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic alterations in the amplitude of low-frequency fluctuation in patients with amyotrophic lateral sclerosis

Abstract: Background Static changes in local brain activity in patients suffering from amyotrophic lateral sclerosis (ALS) have been studied. However, the dynamic characteristics of local brain activity are poorly understood. Whether dynamic alterations could differentiate patients with ALS from healthy controls (HCs) remains unclear. Methods A total of 54 patients with ALS (mean age = 48.71 years, male/female = 36/18) and 54 (mean age = 48.30 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
3
11
0
Order By: Relevance
“…In the current study, the decreased ALFF in the PSMA was highly consistent with the results from previous observations, including decreased glucose metabolism in 18 F‐FDG PET studies (Claassen, Josephs, & Peller, 2010; Pagani et al, 2014), decreased activity of α , β , and θ frequency bands of EEG study (Dukic et al, 2019), as well as decreased ALFF in RS‐fMRI studies (Luo et al, 2012; Ma et al, 2020; Sako et al, 2017). The consistent cross‐modality finding regarding decreased PSMA activity in ALS patients demonstrated that sensorimotor activity reduction is a robust feature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the decreased ALFF in the PSMA was highly consistent with the results from previous observations, including decreased glucose metabolism in 18 F‐FDG PET studies (Claassen, Josephs, & Peller, 2010; Pagani et al, 2014), decreased activity of α , β , and θ frequency bands of EEG study (Dukic et al, 2019), as well as decreased ALFF in RS‐fMRI studies (Luo et al, 2012; Ma et al, 2020; Sako et al, 2017). The consistent cross‐modality finding regarding decreased PSMA activity in ALS patients demonstrated that sensorimotor activity reduction is a robust feature.…”
Section: Discussionsupporting
confidence: 90%
“…The huge heterogeneity in disease progression is probably one of the critical factor that brings uncertainty to in vivo ALS studies, especially for resting‐state fMRI (RS‐fMRI) that detects the neuropathological spontaneous brain activity (Greicius, 2008). While some studies have found consistent reduction of RS‐fMRI local activity (Luo et al, 2012; Ma et al, 2020; Sako et al, 2017) which were highly in line with hypo‐glucose metabolism (Pagani et al, 2014) as well as decreased neural oscillation (Dukic et al, 2019) in the primary sensorimotor area (PSMA), many other studies have reported inconsistent or even contrary results of resting‐state functional connectivity (FC) in the PSMA of ALS patients. For example, a number of studies have reported decreased FC (Fekete, Zach, Mujica‐Parodi, & Turner, 2013; Jelsone‐Swain et al, 2010; Mohammadi et al, 2009; Tedeschi et al, 2012) in ALS patients, yet almost equal number of studies showed increased FC (Basaia et al, 2020; Douaud, Filippini, Knight, Talbot, & Turner, 2011; Menke, Proudfoot, Talbot, & Turner, 2018).…”
Section: Introductionmentioning
confidence: 85%
“…Hence, on the one hand, comparing our results with previous results, that were based on power-spectra or static connectivity, is not trivial. On the other hand, preliminary evidence from fMRI shows altered low-frequency brain dynamics in ALS 59 , which corroborates our results (given the comparable time-scales). However, given the different technique and type of analysis, comparing the results should be done cautiously.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 91%
“…In a previous study, excellent performance with an accuracy of 95.37% was achieved when ALFF maps were employed, followed by ReHo, fALFF, and DC. Ma X. et al (2020) chose 54 amyotrophic lateral sclerosis participants and used ALFF and d-ALFF as the SVM classification feature, and the classification accuracy was 79.63%. From what have been listed above, a reliable conclusion can be drawn that SVM has relatively high accuracy compared with traditional methods to differentiate the patients from healthy subjects.…”
Section: Introductionmentioning
confidence: 99%